(untitled) (Olhares, 2020)
This is an essay-report, a text about artistic actions in the 2020 pandemic of Covid 19 and the urgency of new pedagogical strategies for Body Expression work. In it, I report my experience with students at the Célia Helena Arts Center. I consider the importance of the deep work of body awareness as vital, as well as, the meeting and the creative exchange with other people, even through virtual platforms. I highlight the essence of artistic making considering its continuity is a poetic survival.